2021
DOI: 10.3390/ma14195467
|View full text |Cite
|
Sign up to set email alerts
|

Printing of Zirconia Parts via Fused Filament Fabrication

Abstract: In this work, a process chain for the fabrication of dense zirconia parts will be presented covering the individual steps feedstock compounding, 3D printing via Fused Filament Fabrication (FFF) and thermal postprocessing including debinding and sintering. A special focus was set on the comprehensive rheological characterization of the feedstock systems applying high-pressure capillary and oscillation rheometry. The latter allowed the representation of the flow situation especially in the nozzle of the print he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 47 publications
2
19
0
1
Order By: Relevance
“…Among the various AM techniques that be used for ceramic parts fabrication (threedimensional printing (3DP) [6], stereolithography (SLA) [7][8][9], 3D gel-printing [10], a robocasting technique [11], direct inkjet printing (DIP) [12,13] and fused deposition modeling (FDM) [14,15], etc. ), digital light processing (DLP) [2,5,14,[16][17][18][19][20][21][22] is one of the most promising techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Among the various AM techniques that be used for ceramic parts fabrication (threedimensional printing (3DP) [6], stereolithography (SLA) [7][8][9], 3D gel-printing [10], a robocasting technique [11], direct inkjet printing (DIP) [12,13] and fused deposition modeling (FDM) [14,15], etc. ), digital light processing (DLP) [2,5,14,[16][17][18][19][20][21][22] is one of the most promising techniques.…”
Section: Introductionmentioning
confidence: 99%
“…The composite filaments can then be melted and extruded through nozzles for printing. [13][14][15][16][17] Several printing parameters, including the composition of filaments and the printing rate, have been surveyed to optimize the performance of printed ceramics. [18,19] Finally, the slurries may also be directly extruded through a fine nozzle to form the desired structures.…”
Section: Doi: 101002/adem202300445mentioning
confidence: 99%
“…5 illustrates the schematic of the fused deposition technology with two types of raw material: filament and granule. In both cases, the feedstock is composed of the ceramic powder (usually around 40-50 vol%) and multicomponent binders usually containing a thermoplastic (ethylene vinyl acetate [100][101][102], polylactic acid [103], polyvinyl butyral [22,104], polyolefin [105,106], lowdensity polyethylene [107]), surfactant (stearic acid [102,104,107,108]), and plasticizer (polyethylene glycol [22,103,104]). This material is heated to just above the melting point of the polymer.…”
Section: Fused Depositionmentioning
confidence: 99%
“…They have shown that is possible to process different ceramic materials (alumina [101,102], mullite [100,131], barium titanate [132], and PZT [132]) in ordinary commercial printers. Fused filament fabrication proved to be capable to produce dense ceramic parts (~99%) [ firing shrinkage usually ranges between 17% and 23% [101,102,104,107,111]. A surface roughness (Ra) of around 10 μm can be reached with the process [111,112].…”
Section: Fused Depositionmentioning
confidence: 99%